Assessing Gender Inequality and Lack of Women and Women of Colour in Upper Management Positions in Transport for London, United Kingdom - Okoronta, Ifeoma (Digital Repository of Theses, 2024)
Gender inequality and the underrepresentation of women in upper management positions pose significant challenges within organizations, hindering progress towards achieving gender equity and diversity. The general objective of this study is to assess gender inequality and lack of women and women of colour in upper management positions in Transport for London. Two theoretical frameworks guide the study namely: Intersectionality, which explores how multiple social identities intersect to create unique experiences, and Social Role theory, which examines how societal norms shape gender roles and behavior. The research design is cross-sectional design within the mixed methods approach. The study population consists of all employees at Transport for London, with a sample size of 80 determined statistically. A multi-stage cluster sampling method was used to select participants from four subsidiaries and eight departments in the organisation. Data were collected using questionnaires for quantitative data and in-depth interviews for qualitative data. All qualitative data collected was analyzed and arranged in themes. Quantitative data on the other hand was analyzed using descriptive statistics. The results of the study include that barriers to equal representation of gender in the workplace included limited female mentors in top management (31.2%) and perceptions of unequal consideration for both men and women for positions (43.8%). Discriminatory practices against women of colour were reported, including racial references by co-workers and perceived qualifications based on skin colour. The Chi-square test results show a statistical significant relationship between men and women responses and men being perceived to be more capable of carrying out official management tasks compared to women(p=0.00), men and women being believed to earn the same salary for the same tasks(p<0.00), both men and women being perceived to have equal opportunities for wage increase (p<0.00)and bonuses as well as human resource decisions being seen as creating barriers for female employees to take on qualified job positions (p=0.00).The study concludes that through continued research, advocacy, and concerted action, meaningful progress can be achieved towards a more equitable and inclusive future for all employees irrespective of their gender or race. Keywords: Gender inequality, women, women of colour, upper management, United Kingdom